Long-term non-invasive ventilation in children. Issue 12 (December 2016) - Amaddeo, Alessandro; Frapin, Annick; Fauroux, Brigitte
Summary: Use of long-term non-invasive ventilation is increasing exponentially worldwide in children of all ages. The treatment entails delivery of ventilatory assistance through a non-invasive interface. Indications for use of non-invasive ventilation include conditions that affect normal respiratory balance (eg, those associated with dysfunction of the central drive or respiratory muscles) and disorders characterised by an increase in respiratory load (eg, obstructive airway or lung diseases). The type of non-invasive ventilation used depends on the pathophysiological features of the respiratory failure. For example, non-invasive ventilation will need to either replace central drive if the disorder is characterised by an abnormal central drive or substitute for the respiratory muscles if the condition is associated with respiratory muscle weakness. Non-invasive ventilation might also need to unload the respiratory muscles in case of an increase in respiratory load, as seen in upper airway obstruction and some lung diseases. Technical aspects are also important when choosing non-invasive ventilation—eg, appropriate interface and device. The great heterogeneity of disorders, age ranges of affected children, prognoses, and outcomes of patients needing long-term non-invasive ventilation underline the need for management by skilled multidisciplinary centres with technical competence in paediatric non-invasive ventilation and expertise in sleep studies and therapeutic education.